2020
DOI: 10.3390/en13236339
|View full text |Cite
|
Sign up to set email alerts
|

Friends or Foes? Political Synergy or Competition between Renewable Energy and Energy Efficiency Policy

Abstract: Energy efficiency measures and the deployment of renewable energy are commonly presented as two sides of the same coin—as necessary and synergistic measures to decarbonize energy systems and reach the temperature goals of the Paris Agreement. Here, we quantitatively investigate the policies and performances of the EU Member States to see whether renewables and energy efficiency policies are politically synergistic or if they rather compete for political attention and resources. We find that Member States, espe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…The pressing issue of finite resources and climate change has also generated a prominent body of literature. Many studies deal with sustainable or renewable energy from a multidisciplinary point of view [24,[26][27][28][29][30][31][32]. Another relevant strand of literature addresses energy policy matters [31][32][33][34][35], incorporating aspects related to innovation and development in the energy sector [36][37][38][39][40].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The pressing issue of finite resources and climate change has also generated a prominent body of literature. Many studies deal with sustainable or renewable energy from a multidisciplinary point of view [24,[26][27][28][29][30][31][32]. Another relevant strand of literature addresses energy policy matters [31][32][33][34][35], incorporating aspects related to innovation and development in the energy sector [36][37][38][39][40].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The policy design element "objectives" describes the specific requirements that are operationalized into formal policy (Cashore & Howlett, 2007). Previous research has shown that states pursue different objectives regarding their technological approach to decarbonization (Komor & Bazilian, 2005;Ollier et al, 2020;Patt et al, 2019). For the energy sector, three broad strategies for decarbonization are available: (i) reconfiguration of the existing system and a transition to lower-carbon options (e.g., modernizing coal power plants, transitioning from coal to gas power, nuclear energy, or carbon capture and storage) in a technology-neutral approach, (ii) deployment of renewables, and (iii) the reduction of demand, and therefore consumption, through energy-efficiency measures (IPCC, 2018).…”
Section: H3mentioning
confidence: 99%
“…Not surprisingly, these two types of initiatives have been discussed together, and their interactions have been studied. While synergies were not found in certain policy settings (Ollier et al 2020), there may still be advantages to corporations (Prindle et al 2007). Households may similarly face conflicting effects depending on the setting (Dato 2018).…”
Section: Re Sourcing and Eementioning
confidence: 99%
“…While there is prior work on the relationship between RE and EE (see detailed review in Section 2), it has largely been cross-sectional and focused at the household (Dato 2018) or the macroeconomic level (Ollier et al 2020). The former is based on household survey data that does not capture investment decisions, and the latter uses variations across countries to estimate the relationship, which is too broad to yield actionable insight.…”
Section: Introductionmentioning
confidence: 99%